KUFS-USM JAPANESE CULTURAL CENTRE: SYMBOL OF BILATERAL CULTURAL RELATIONS AND COLLABORATIONS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, March 2016 The official launch of the KUFSUSM Japanese Cultural Centre by the Yang diPertua Negeri Pulau Pinang, Tuan Yang Terutama Tun Dato’ Seri Utama (Dr.) Haji Abdul Rahman bin Haji Abbas recently further strengthened the cultural relations and collaborations between Universiti Sains Malaysia (USM) and Kyoto University of Foreign Studies (KUFS), Japan.